Biofilm Formation and Motility Depend on the Nature of the Acinetobacter baumannii Clinical Isolates - Vijayakumar, Saranya; Rajenderan, Sangeetha; Laishram, Shakti; Anandan, Shalini; Balaji, Veeraraghavan; Biswas, Indranil (Frontiers in Public Health, 2016)
Acinetobacter baumannii is a nosocomial pathogen involved in various infections ranging from minor soft-tissue infections to more severe infections such as ventilator-associated pneumonia and bacteremia. The severity and the type of infections depend on the genetic and phenotypic variations of the strains. In this study, we compared the extent of biofilm formation and motility displayed by 60 multidrug-resistant A. baumannii clinical strains isolated from blood and sputum samples from patients from Southern India. Our results showed that isolates from the sputum samples formed significantly more robust biofilm compared to the blood isolates. On the other hand, we observed that the blood isolates were more motile than the sputum isolates. To the best of our knowledge, this is the first study that systematically evaluated the correlation between these two phenotypic traits and the nature of the isolates.